Sociocultural Inclusion: Conceptual Foundations and Development Trends - D.R. Khalikova; E.V. Khilkevich (Moscow State University of Psychology and Education, 2022)
The formation of inclusive processes in Russian culture sphere is becoming more and more noticeable every year. The article systematizes theoretical and methodological foundations on which modern inclusive practices used in the field of culture are based. It also identifies further development trends in this area. The content of basic concepts of sociocultural inclusion is revealed - the social model of disability, universal design, principles of participation and the accessible environment in a cultural institution. Attention is paid to examples of networking in the field of sociocultural inclusion as a necessary condition for the development of effective and systematic work of cultural institutions with new audiences, in particular, with visitors with ASD in other mental characteristics. Examples of main vectors of cooperation in the field of sociocultural inclusion are given: the involvement of experts with ASD on the creation of special conditions in public spaces, interaction with educational organizations and charitable foundations, which contributes to the emergence of new inclusive programs, the creation of an inter-institutional expert project. It is noted that the main trend in the further development of sociocultural inclusion at this stage is the development of criteria for assessing the effects of introducing practices into the sphere of culture aimed at the integration people with disabilities.